Determination of the Critical Success Factors (CSF) in the implementation of Six Sigma (SS) and its sustainable benefits: Content validity and internal consistency of the measurement instrument. - López, Aida (IGI Global, 2020)
Currently, organizations seek to position themselves in the market as the most competitive and profitable in their branch, through the continuous improvement of their processes, products, and/or services, applying various techniques, tools, and methodologies. Particularly in this chapter, focus on Six Sigma (SS) will be shown, a strategy used in companies to achieve competitive objectives, continuously improving processes. In this sense, it is considered important to identify and know the main factors that are involved in its implementation. Likewise, the organizations are presenting a culture towards the sustainability and the environmental care, derived from this, the methodology used to develop a measurement instrument that allows to identify the CSF in the implementation of SS, the sustainable benefits that can be achieve with correct implementation, the procedure used for the validation of the content of the instrument, the validity of internal consistency and the obtained results.